Viral DNA Synthesis in Cells Infected by Temperature-Sensitive Mutants of Simian Virus 40 - Chou, Janice Yang (1974)
Temperature-sensitive mutants of simian virus 40 (SV40) have been classified as those that are blocked prior to viral DNA synthesis at the restrictive temperature, “early” mutants, and those harboring a defect later in the replication cycle, “late” mutants. Mutants of the A and D complementation groups are early, those of the B, C, and BC groups are late. Our results confirm earlier reports that A mutants are defective in a function required for the initiation of each round of viral DNA synthesis. D mutants, on the other hand, continue viral DNA replication at the restrictive temperature after preincubation at the permissive temperature. The length of time required for D function to be expressed at the permissive temperature—after which infection proceeds unabated on shifting of the cultures to the restrictive temperature—is 10 to 20 h. The viral DNA synthesized in D mutants under these conditions progresses in normal fashion through replicative intermediate molecules to mature component I and II DNA molecules.